Employing ginger extract as an eco-friendly corrosion inhibitor in cementitious materials. (20th December 2019) - Wang, Wanyi; Song, Zijian; Guo, Mingzhi; Jiang, Linhua; Xiao, Beibei; Jiang, Quanguo; Chu, Hongqiang; Liu, Yongqi; Zhang, Yingjie; Xu, Na
Highlights: Ginger extract was innovatively used as a corrosion inhibitor for reinforced concrete. QM/MD methods were used to simulate the adsorption processes of inhibition molecules. The passive films for systems with/without ginger extract were analyzed by XPS. Three possible adsorption mechanisms for ginger corrosion inhibitors were proposed. Abstract: In our recent work, the inhibition effect of ginger extract was preliminarily studied in simulated concrete pore solutions. Now it was applied in cementitious materials to augment the reinforcement corrosion resistance. The inhibition effects of ginger extract and three other commonly used corrosion inhibitors were studied and compared by means of open circuit potential, linear polarization resistance and electrochemical impedance spectroscopy. X-ray photoelectron spectroscopy was used to analyze the chemical compositions of the film formed on the steel bar embedded in the cement mortars. For further understanding the insight of inhibition mechanisms, molecular dynamics and quantum mechanics methods were used to simulate the adsorption processes of the major inhibition molecules onto the surface of steel reinforcement. In addition, the effects of the ginger extract on the flowability and strength of fresh and hardened cement mortars were also examined. The results showed that the ginger extract acting as an effective corrosion inhibitor can lower the corrosion risk of steel bars embedded in cement mortars. The ginger extract's effective corrosion inhibition was mainly attributed to the formation of a carbonaceous organic film on the steel surface. According to the experimental and simulation results, three potential mechanisms of adsorption were proposed. Plus, it was found that the addition of the ginger corrosion inhibitor in cement mortars had a positive effect on the flowability and a negligible negative effect on the strength. The overall findings demonstrated that this ginger extract holds great potential for broader applications in practical engineering.